Why, When, Who, What, How, and Where for Trainees Writing Literature Review Articles - Koons, Gerry L. (Ann Biomed Eng, 2019)
Literature review articles provide a valuable mechanism for remaining informed amidst an ever-increasing body of scientific work. Condensing current advances into this disseminatable form is a critical activity for any research trainee. To systematize this multifaceted process, we present the “why, when, who, what, how, and where” of composing a literature review article. Commentaries include selection of a review topic, conducting modern literature searches using online databases, stepwise strategies for manuscript drafting, and prevention of plagiarism. The current work provides structures and guidance for this fundamental effort which can establish the basis for a trainee’s development of original research objectives.